Sorting versus screening in decentralized markets with adverse selection - Sarah Auster; Piero Gottardi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We study the role of traders' meeting capacities in decentralized markets with adverse selection. Uninformed customers choose trading mechanisms in order to find a provider for a service. Providers are privately informed about their quality and aim to match with one of the customers. We consider a rich set of meeting technologies and characterize the properties of the equilibrium allocations for each of them. In equilibrium, different provider types can be separated either via sorting - they self-select into different submarkets - or screening within the trading mechanism, or a combination of the two. We show that, as the meeting technology improves, the equilibrium features more screening and less sorting. Interestingly, this reduces both the average quality of trade as well as the total level of trade in the economy. The trading losses are, however, compensated by savings in entry costs, so that welfare increases.
Keywords: C78; D44; D83; 330; Competitive Search; Adverse Selection; Market Segmentation